Comparison of enzymax pax and sodium hypochlorite as dental unit waterline disinfectant in UPCD clinics - Aquino, Marjorie Christy A.
INTRODUCTION:One-step, self-etch adhesives (SEA) have become increasingly popular because of the simplified application technique. Furthermore, SEAs are reported to perform comparatively to etch-and-rinse (ER) and self-etch primer (SEP) systems. The ability of SEA systems to perform as well as the other systems in vivo can be attributed to several factors including surface pretreatment with 37% phosphoric acid. The present study compared the enamel and dentin SBS of a SEA system following the manufacturer?s instruction and the same SEA with surface pretreatment using 37% phosphoric acid prior to application.